2023
DOI: 10.1002/eem2.12500
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity Induced by Oxygen Vacancies in Rhombohedral ZrO2 Thin Films

Abstract: Rhombohedral phase HfxZr1‐xO2 (HZO, x from 0 to 1) films are promising for achieving robust ferroelectric polarization without the need for an initial wake‐up pre‐cycling, as is normally the case for the more commonly studied orthorhombic phase. However, a large spontaneous polarization observed in rhombohedral films is not fully understood, and there are also large discrepancies between experimental and theoretical predictions. In this work, in rhombohedral ZrO2 thin films, we show that oxygen vacancies are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…This distorted t to r phase transition might offer a new path to investigate the high polarization reported experimentally in the r phase, which is in discrepancy with DFT predictions of low polarization. 34,92 However, other factors, such as oxygen vacancies and the interaction between the ZrO 2 film and the substrate, may also contribute to stabilizing the rhombohedral phase.…”
Section: Resultsmentioning
confidence: 99%
“…This distorted t to r phase transition might offer a new path to investigate the high polarization reported experimentally in the r phase, which is in discrepancy with DFT predictions of low polarization. 34,92 However, other factors, such as oxygen vacancies and the interaction between the ZrO 2 film and the substrate, may also contribute to stabilizing the rhombohedral phase.…”
Section: Resultsmentioning
confidence: 99%
“…investigated the influence of oxygen vacancies on the ferroelectric polarization of both the r and t ‐phases of ZrO 2 , revealing that oxygen vacancies can indeed promote a polarization in the t ‐phase of ZrO 2 . [ 24 ] However, at two distinct oxygen vacancy concentrations of 4.16% and 0.51%, the resulting polarization was found to remain lower than 1 µC cm −2 . [ 24 ] Thus, oxygen vacancies alone cannot account for the polarization levels measured in our ZrO 2 films (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…[ 24 ] However, at two distinct oxygen vacancy concentrations of 4.16% and 0.51%, the resulting polarization was found to remain lower than 1 µC cm −2 . [ 24 ] Thus, oxygen vacancies alone cannot account for the polarization levels measured in our ZrO 2 films (Figure 4). Another factor is electric‐field induced oxygen migration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] Although HZO shows the largest polarisation values, ZrO 2 is much more abundant in nature and therefore is a more appealing choice for large-scale use. [21] The emergence of the ferroelectricity in ZrO 2 arises from the o-phase (space group: Pca2 1 ) [22] and the polar rhombohedral (r-)phase (space group: R3m) [23] that can be only achieved in a constrained environment in the thin film form. It was recently revealed that ferroelectricity and hysteretic polarization switching can be achieved in ultrathin ZrO 2 with the fluorite-structure unit-cell size [24] for a film thickness of 5 Å.…”
Section: Introductionmentioning
confidence: 99%